PMMA/SAN and SAN/PBT nanoblends obtained by blending extrusion using thermodynamics and microrheogy basis - L. C. Costa; E. Hage; A. Ternes Neto (eXPRESS Polymer Letters, 2014)
Styrene-Acrylonitrile (SAN) copolymer has been blended to poly(methyl methacrylate) (PMMA) and to poly(butylene terephthalate) (PBT) to obtain polymer nanoblends based on thermodynamics and microrheological aspects. PMMA/SAN and SAN/PBT blends show miscibility windows for a specific range of acrylonitrile (AN) content in the SAN copolymer. The phase diagram for both blends has been calculated using the interaction energy density parameter B as function of AN content in the SAN. A critical interaction energy density parameter, Bcrit, was also calculated to find the miscibility window for both SAN blends. For some of the used SAN in the blends it was possible to obtain nanoblends as the AN content would allow B values close to the Bcrit. For immiscible PMMA/SAN and SAN/PBT blends the disperse particle size was predicted using suitable equations and it was observed by transmission electron microscopy (TEM). Acrylic copolymers were used as compatibilizer to modify the interfacial tension and reduce the disperse phase dimensions. The compatibilizer has shown strong effect by reducing the interfacial tension and by preventing the coalescence effect. The compatibilized blends have shown disperse particle size within the nanoscale.